Juxtapositions: Pierre Boulez: Eclat & Sur incises - Boulez, Pierre 1925-2016; Scheffer, Frank; Sommer, Andy (Idéale audience international)
'Juxtapositions' is a unique DVD collection focusing on contemporary music. Each DVD explores the world of a particular composer via one or more works with the composers and their most famous interpreters playing an active part in the process of elucidation. We travel from Pierre Boulez, Elliott Carter, Philip Glass to Olivier Messiaen, composers who reshaped the contours of our musical landscape in the 20th century.Works:Eclat for 15 Instruments by Pierre Boulez Conductor: Ed Spanjaard Orchestra/Ensemble: Nieuw Ensemble Period: 20th Century Written: 1965Sur Incises by Pierre Boulez Conductor: Pierre Boulez Orchestra/Ensemble: Ensemble InterContemporain Period: 20th Century Written: 1996/1998